Inline dual‐echo T2 quantification in brain using a fast mapping reconstruction technique. (26th August 2022) - Snyder, Jeff; Seres, Peter; Stobbe, Robert W.; Grenier, Justin G.; Smyth, Penelope; Blevins, Gregg; Wilman, Alan H.
Abstract : T2 mapping from 2D proton density and T2–weighted images (PD‐T2) using Bloch equation simulations can be time consuming and introduces a latency between image acquisition and T2 map production. A fast T2 mapping reconstruction method is investigated and compared with a previous modeling approach to reduce computation time and allow inline T2 maps on the MRI console. Brain PD‐T2 images from five multiple sclerosis patients were used to compare T2 map reconstruction times between the new subtraction method and the Euclidean norm minimization technique. Bloch equation simulations were used to create the lookup table for decay curve matching in both cases. Agreement of the two techniques used Bland–Altman analysis for investigating individual subsets of data and all image points in the five volumes (meta‐analysis). The subtraction method resulted in an average reduction of computation time for single slices from 134 s (minimization method) to 0.44 s. Comparing T2 values between the subtraction and minimization methods resulted in a confidence interval ranging from −0.06 to 0.06 ms (95% of values were within ± 0.06 ms between the techniques). Using identical reconstruction code based on the subtraction method, inline T2 maps were produced from PD‐T2 images directly on the scanner console. The excellent agreement between the two methods permits the subtraction technique to be interchanged with the previous method, reducing computation time and allowing inline T2 map reconstruction based on Bloch simulations directly on the scanner. Abstract : A fast T2 mapping reconstruction technique based on Bloch equation modeling of the dual spin‐echo PD‐T2 sequence, allowing T2 map reconstruction of 50 slice datasets in 22 s. Comparison between new and previous methods using Bland–Altman analysis of five multiple sclerosis patients resulted in excellent agreement, with 95% of T2 values within ± 0.06 ms. The algorithm was replicated on the MRI console to produce inline reconstruction of T2 maps included in the imaging study for efficient clinical use.